2017
DOI: 10.3389/fpsyg.2017.01219
|View full text |Cite
|
Sign up to set email alerts
|

Class Collective Efficacy and Class Size as Moderators of the Relationship between Junior Middle School Students’ Externalizing Behavior and Academic Engagement: A Multilevel Study

Abstract: This study examined the relationship between externalizing behavior and academic engagement, and tested the possibility of class collective efficacy and class size moderating this relationship. Data were collected from 28 Chinese classrooms (N = 1034 students; grades 7, 8, and 9) with student reports. Hierarchical linear modeling was used to test all hypotheses and results revealed a negative relationship between externalizing behavior and academic engagement; class collective efficacy was also significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Bryk and Schneider's (2002) more Putnamesque study of social capital in schools showed that schools with high levels of 'relational trust' delivered reduced truancy and improved learning outcomes. Finally, Tian et al (2017), in a wonderful Chinese study, showed that classroom collective efficacy helped students to become more active and effective learners, better at self-regulating their self-efficacy. The combination of high classroom collective efficacy and small class sizes delivered collaborative, relational learning that simultaneously produced improved learning and reduced delinquency and aggression (Tian et al 2017).…”
Section: Institutionalised Contagions Of Collective Efficacymentioning
confidence: 99%
“…Bryk and Schneider's (2002) more Putnamesque study of social capital in schools showed that schools with high levels of 'relational trust' delivered reduced truancy and improved learning outcomes. Finally, Tian et al (2017), in a wonderful Chinese study, showed that classroom collective efficacy helped students to become more active and effective learners, better at self-regulating their self-efficacy. The combination of high classroom collective efficacy and small class sizes delivered collaborative, relational learning that simultaneously produced improved learning and reduced delinquency and aggression (Tian et al 2017).…”
Section: Institutionalised Contagions Of Collective Efficacymentioning
confidence: 99%
“…ELLs exhibit stability and effort when engaged in doing homework or activities, even in the absence of internal rewards (10). Academically engaged students have more ability to cope with academic stress and are more satisfied (11) and as described by Kaplan et al, they are attentive and participate in class discussions, exert effort in class activities, and exhibit interest and motivation in learning (12). There is an agreement among the experts that student engagement is a multi-dimensional concept (13,14) and its dimensions include behavioral, emotional, and cognitive subtypes (13,15).…”
Section: Introductionmentioning
confidence: 99%